TESTING THE MEDIATION ROLE OF PUBLIC SERVICE QUALITY IN THE RELATIONSHIP BETWEEN INTERNAL CONTROL IMPLEMENTATION AND GOOD GOVERNMENT GOVERNANCE OF THE REGIONAL GOVERNMENT OF NORTH SUMATRA USING SEM-PLS - Nasution, Dito Aditia Darma; Erlina, Erlina; Muda, Iskandar; Yahya, Idhar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The North Sumatra Regional Government has a significant responsibility in organizing effective and accountable governance for the welfare of its people. The implementation of internal control (ICI) is crucial in achieving this goal. Effective internal control can help optimize resource management and prevent fraud and abuse of power. This study examines the mediating role of public service quality (PSQ) in the relationship between internal control implementation and good governance (GGG) in PDSU. The analysis using the SEM-PLS model shows that internal control implementation has a significant direct influence on public service quality. However, the direct influence of public service quality on good governance is not statistically significant. The implication of these findings is the importance of enhancing internal control implementation to improve public service quality, even though the direct influence of public service quality on good governance is not statistically supported in this study.